Proceso de atención de enfermería en neonato con asfixia severa. - Bastidas Mora, Solange Beatriz (2023)
Below is a case study based on the application of the nursing process in a newborn with severe neonatal asphyxia, the same one who was born in serious clinical conditions, as a result of a cesarean section, a newborn assessed at 38 weeks of gestation. Most perinatal morbidity is related to hypoxic, traumatic, infectious and pharmacological disorders, the most frequent of which are those associated with lack of oxygen. Perinatal asphyxia is a serious pathology characterized by cardiorespiratory depression, secondary to hypoxemia and /or fetal tissue ischemia. Pathophysiologically, there is hypoxemia, CO2 retention and metabolic acidosis that causes encephalopathy, resulting in infantile cerebral palsy (ICP). The damage caused by asphyxia will ultimately depend on the extent to which the delivery of oxygen to the tissues is altered, which depends of the amount of oxygen in arterial blood, which is determined by the concentration of hemoglobin. Through the nursing care process, the specific objective is to identify the main problems that intervene in the appearance of neonatal asphyxia, where we will have as the main diagnosis an ineffective respiratory pattern, where these actions will be executed, following up on the treatment designated by the doctor by evaluating the results obtained for the recovery of the neonate, improving their hospital stay, thus being in good health conditions for their hospital discharge.